Kedudukan Qanun dalam Sistem Pemerintahan Daerah dan Mekanisme Pengawasannya - Jum Anggriani (Fakultas Hukum Universitas Islam Indonesia, 2011)
This research is focused on the issue of supervision of Qanun as a realization of Central Government authorithy over special autonomy in Nangroe Aceh Darussalam. This research uses analytic descriptive method which gives illustration on scope and opinion of the Central Government supervision over Qanun in Nangroe Aceh Darussalam. This research used juridical normative method as well through legislation approach. This research concludes that for the purpose of supervisory, Central Government may suspend or annul Qanun in the event of contradiction to the related legislation. Preventive supervision is performed on the Regional Government policy which regulates revenue budget and regional expenditure, regional tax, and other regulation that may cause high economical cost.